Resolution of massive left atrial appendage thrombi with rivaroxaban before balloon mitral commissurotomy in severe mitral stenosis: A case report and literature review. Issue 49 (December 2016) - Li, Yuechun; Lin, Jiafeng; Peng, Chen
Abstract: Rationale: Data on nonvitamin K antagonist oral anticoagulant being used for the treatment of LAA thrombi are limited only in nonvalvular atrial fibrillation. There are no data on the antithrombotic efficacy and safety of nonvitamin K antagonist oral anticoagulant in the resolution of left atrial appendage (LAA) thrombi in patients with rheumatic mitral stenosis. Patient concerns: A 49-year-old woman with known rheumatic mitral stenosis and atrial fibrillation was referred for percutaneous transvenous mitral commissurotomy because of progressive dyspnea on exertion over a period of 3 months. Diagnoses: Transesophageal echocardiography (TEE) demonstrated a large LAA thrombus protruding into left atria cavity before the procedure. Interventions: Direct factor Xa (FXa) inhibitor rivaroxaban (20 mg/d) was started for the patient. After 3 weeks of rivaroxaban treatment TEE showed a relevantly decreased thrombus size, and a complete thrombus resolution was achieved after 5 weeks of anticoagulant therapy with the FXa inhibitor. Outcomes: To the best of our knowledge, this is the first documented case of large LAA thrombus resolution with nonvitamin K antagonist oral anticoagulant in severe mitral stenosis, and in which percutaneous transvenous mitral commissurotomy was performed subsequently. Lessons: The report indicated that rivaroxaban could be a therapeutic option for mitral stenosis patients with LAA thrombus. Further study is required before the routine use of rivaroxaban in patients with rheumatic mitral stenosis and atrial fibrillation.